(untitled) (Swiss Medical Weekly, 2012)
Ageing of the world’s population raises important questions about the utilisation of the health care system. It is not clear how much should be invested in the last years of life whereas the costs are known to increase in parallel. Since intensive care units (ICU) are costly with highly specialised personnel, it seems of paramount importance that they would be used efficiently. Indeed, in the present context of predicted shortage of physicians in Switzerland, society and politics will need evidence that the care provided by ICUs is appropriate. There is no explicit limitation of care in any country according to age and nonagerians are admitted nowadays into ICUs with critical illness. This review article will address the question of elderly patients in ICU and their outcome. Outcome does not imply surviving ICU but only later during the hospital stay and after discharge. Furthermore, we emphasise the need of examining not solely the hospital survival but the quality of life of the patients when they return to their real life. The fundamental questions are actually “Do they go back to life?” “What is life for elderly people?” These questions lead to more basic questions such as “Are they able to go back home or are they institutionalised? How is their quality of life and functional status after ICU?”. We tried to address these questions through the existing literature and our experience while caring for these particular patients. Some clues on the prognostic factors related to their outcome are reported.